Evaluation of the Characteristics of Connection when Welding the Mg Alloy AZ60 - Lim, Byung-Chul; Kim, Dae-Hwan; Lee, Han-Seop; Park, Sang-Heup (International Journal of Engineering and Technology, 2019)
In this study, the mechanical characteristics of the microstructure were analyzed on the butt joint of AZ60 magnesium material extruded using the gas metal arc welding (GMAW) and gas tungsten arc welding (GTAW) processes. The tensile test results showed that fractures occurred in the welding joint area in both processes and seemed to be due to brittle fracture. The average yield strengths obtained with GMAW and GTAW were 143.29MPa (84.29%) and 102.73 (60.43%), respectively (relative to the base metal). The yield strength with GMAW was 40.56MPa (23.86%) higher than with GTAW. Both processes led to decreased micro hardness. The minimum microhardness values in the fusion zone were Hv 46.7 and Hv 43.6 with GMAW and GTAW, respectively (relative to the base metal). The minimum microhardness with the GMAW process was 5.64% greater than with the GTAW process. The size of the grain boundary in the heat affected zone with the GMAW process, was smaller than with the GTAW process. The GMAW process is superior to the GTAW process, in terms of productivity and quality, in cases where automatic welding of magnesium alloy is used for items such as automobile seat frames.Â